The mediating role of mental toughness in sport - Nicholls, A. R.; Perry, J. L.; Jones, L.; Sanctuary, C.; Carson, F.; Clough, P. J. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: We conducted two studies that examined different models, which included mental toughness and psychological constructs that have been found to be related to this construct.